Стан пошуково-розвідувальних робіт та проблеми уточнення моделей покладів вуглеводнів - Чебаненко, І.І.; Дем'яненко, І.І.; Крупський, Б.Л.; Гладун, В.В.; Максимчук, П.Я.; Дем'яненко (мол.), І.І.; Клочко, В.П.; Смирнов, І.В.; Зейкан, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
The problems of geological models of the deposits of hydrocarbons and the means of their solution during the survey of oil and gas on the basis of studying the EW condition at the East petroleum region are shown.